Sanggar Nadi sebagai Sarana Penguatan Keterampilan dan Bakat Anak-anak: Tinjauan terhadap Implementasi Program UNNES GIAT 9 Desa Ternadi - Mawarrina Nur Aini; Andi Irwan Benardi; Faristin Nabila Priwahyuni; Muizzatul Mila; Nor Laila Sifa; Aprilia Dini (Jurnal Bina Desa, 2026)
Sanggar Nadi is a program initiated by students from Universitas Negeri Semarang (UNNES) as part of the UNNES GIAT 9 framework. This program was created to improve access to quality education and self-development facilities for children in Ternadi Village, which are often limited. The purpose of the program is to enhance children's skills and develop their talents through educational and creative activities, with the children as the primary focus of the service. The methods used in this program include initial observations to map the children's interests and talents, followed by intensive mentoring through activities such as learning acting, story writing, reading, and dancing. The activities were carried out by designing and implementing a program based on arts and culture, with the aim of strengthening children's skills and interests. The results of the program showed that Sanggar Nadi successfully made a positive impact on the development of children's skills and talents, although there are still challenges to be addressed, such as the need to improve program management and ensure the sustainability of the activities. The program also successfully created creative products such as folktales and dance performances that reflect local cultural values.